The Role of MSMEs in Driving the Economy of Singkawang: A Systematic Literature Review - Haryanto, Haryanto; Nurainie, Nurainie; Querelia, Marcella; Wijaya, Yordanus Rangga (Jurnal Ilmiah Raflesia Akuntansi, 2024)
The study emphasizes the important role of Micro, Small, and Medium Enterprises (MSMEs) in driving economic growth in Singkawang City, West Kalimantan. Using a Systematic Literature Review (SLR) approach, the research gathered and assessed data from various sources to understand the impact of MSMEs in the local context. The results indicate that MSMEs significantly contribute to increased production, income, and employment. The tourism sector, particularly through cultural festivals such as Cap Go Meh, also plays a crucial role in boosting regional income and economic growth. The study concludes that MSMEs and the tourism sector are essential for the economic development of Singkawang City. Furthermore, the participation of MSMEs in cultural festivals enhances tourism sector income and contributes to economic growth through the hotel and trade sectors. These findings have important implications for policymakers, business professionals, and academics, providing valuable insights for developing more effective strategies to support MSMEs and the tourism sector. Understanding the pivotal role of MSMEs and cultural festivals in local economic growth can guide the creation of targeted policies to achieve inclusive and sustainable economic development in Singkawang